PR gene families of citrus: their organ specific-biotic and abiotic inducible expression profiles based on ESTs approach - Campos, Magnólia A.; Rosa, Daniel D. [UNESP]; Teixeira, Juliana Érika C.; Targon, Maria Luisa P.N.; Souza, Alessandra A.; Paiva, Luciano V.; Stach-Machado, Dagmar R.; Machado, Marcos A. (Sociedade Brasileira de Genética, 2007)
In silico expression profiles, of the discovered 3,103 citrus ESTs putatively encoding for PR protein families (PR-1 to PR-17), were evaluated using the Brazil citrus genome EST CitEST/database. Hierarchical clustering was displayed to identify similarities in expression patterns among citrus PR-like gene families (PRlgf) in 33 selected cDNA libraries. In this way, PRlgf preferentially expressed by organ and citrus species, and library conditions were highlighted. Changes in expression profiles of clusters for each of the 17 PRlgf expressed in organs infected by pathogens or drought-stressed citrus species were displayed for relative suppression or induction gene expression in relation to the counterpart control. Overall, few PRlgf showed expression 2-fold higher in pathogen-infected than in uninfected organs, even though the differential expression profiles displayed have been quite diverse among studied species and organs. Furthermore, an insight into some contigs from four PRlgf pointed out putative members of multigene families. They appear to be evolutionarily conserved within citrus species and/or organ- or stress-specifically expressed. Our results represent a starting point regarding the extent of expression pattern differences underlying PRlgf expression and reveal genes that may prove to be useful in studies regarding biotechnological approaches or citrus resistance markers.
Keywords: citrus; functional genome; ests; gene expression profiles; pathogenesis-related proteins; defense genes